Identifying novel phenotypes of vulnerability and resistance to activity‐based anorexia in adolescent female rats. Issue 7 (13th July 2013) - Barbarich‐Marsteller, Nicole C.; Underwood, Mark D.; Foltin, Richard W.; Myers, Michael M.; Walsh, B. Timothy; Barrett, Jeffrey S.; Marsteller, Douglas A.
ABSTRACT Objective Activity‐based anorexia is a translational rodent model that results in severe weight loss, hyperactivity, and voluntary self‐starvation. The goal of our investigation was to identify vulnerable and resistant phenotypes of activity‐based anorexia in adolescent female rats. Method Sprague‐Dawley rats were maintained under conditions of restricted access to food (N = 64; or unlimited access, N = 16) until experimental exit, predefined as a target weight loss of 30–35% or meeting predefined criteria for animal health. Nonlinear mixed effects statistical modeling was used to describe wheel running behavior, time to event analysis was used to assess experimental exit, and a regressive partitioning algorithm was used to classify phenotypes. Results Objective criteria were identified for distinguishing novel phenotypes of activity‐based anorexia, including a vulnerable phenotype that conferred maximal hyperactivity, minimal food intake, and the shortest time to experimental exit, and a resistant phenotype that conferred minimal activity and the longest time to experimental exit. Discussion The identification of objective criteria for defining vulnerable and resistant phenotypes of activity‐based anorexia in adolescent female rats provides an important framework for studying the neural mechanisms that promote vulnerability to or protection against the development of self‐starvation and hyperactivity during adolescence. Ultimately, future studies using these novel phenotypes may provide important translational insights into the mechanisms that promote these maladaptive behaviors characteristic of anorexia nervosa. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:737–746)